PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP TINGKATKEPATUHAN PENGUNGKAPAN WAJIB KONVERGENSI IFRS PADAPERUSAHAAN HOTEL, RESTORAN DAN PARIWISATA YANG TERDAFTAR DIBURSA EFEK INDONESIA PERIODE 2014-2018 - Diska Asmarni; Irni Yusnita (Jurnal Ekonomi Sakti, 2019)
The purpose of the this research is to test the influence the mechanism of corporate governance to the level of mandatory disclosure compliance convergence of IFRS. The mechanism of corporate governance is measured by the number of board commissioner meetings, the proportion of independent commissioners, the number of members of board commissioners, the number of audit committees, the number of audit committee meetings and managerial ownership. The sampling method used in this research is a purposive sampling method and obtained a sample of 10 companies from 2014-2018. The results of this showed that the number of members of board commissioner and managerial ownership have significantly influence to the level of mandatory disclosure compliance convergence of IFRS. The number of board commissioner meetings, the proportion of independent commissioners, the number of audit committees, and the number of audit committee meetings does not significantly influence to the level of mandatory disclosure compliance convergence of IFRS.